Bronze Age Hoard of Axes Found in Oficjałów, Opatów Commune, Świętokrzyskie Voivodeship - Florek, Marek (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2016)
In 2011, a hoard consisting of 3 bronze flanged axes (with a funnel-shaped face), so called Bohemian type was found in the village Oficjałów, Opatów commune, Świętokrzyskie Voivodeship. The hoard can be dated to the middle period of the Bronze Age (HA1 phase). Regarding Polish territories, similar axes, mainly discovered in hoards, rarely individually, occasionally in burial complexes, are known mostly from Silesia, and also from western Lesser Poland, rarely from other regions. This is the third hoard of bronze items discovered on the Sandomierz Uplands and the first one containing axes. It may be the evidence of influence of the Western Lesser Poland group of the Lusatian culture (possibly even in the form of infiltration of small groups of people) on “Lusatian settlement” appearing on the Sandomierz Uplands. What is more, we cannot exclude the possibility that, together with other hoards and individual bronze artefacts from this area, it is the evidence of contacts of the local group of the Trzciniec culture with the “Lusatian” environment in the Sandomierz Upland.
Skarb siekier z epoki brązu z Oficjałowa, gm. Opatów, woj. świętokrzyskie
Keywords: Bronze axes; Sandomierz Uplands; Lusatian culture